Caracterização e tendências climáticas da cidade de Patos (Paraíba) e consequências para a energia fotovoltaica - Farias Neto, José Ribeiro (2020)
Among the main renewable sources, photovoltaic energy is increasingly reaching the prominent position in Brazil, due to the country's high solar potential, especially in the Northeast region. Energy production from renewable energy sources is vulnerable to climate change, but the changes do not affect a pattern of behavior. In this context, the present study sought to identify changes in the potential of photovoltaic production in the city of Patos-PB, due to the influence of climate changes. Through statistical tests non-parametric Mann-Kendall and Sen, users can get information on trends in climate parameters and photovoltaic electricity production during the study period. The average temperature shown in the trends of significant increase in March (p<0.10), May (p<0.10), June (p<0.05) and August (p<0.01). There is already cloudiness that shows a significant tendency to decrease in March and September (p <0.05). The available data series on solar radiation is short and insufficient for reduced trend variations. The records of this scalable element in Patos are initiated from the installation of the INMET automatic station, in 2007. Comparison between the first 10 years (1975-1984) and the last 10 years (2009-2018) of the series, there was a reduction of 0.34 % in the production of electricity. The most unfavorable months for production were in June and July, and the most promising in October and November. It was concluded that studies of determinant climatic trends are important that can demonstrate regional changes and their impacts on energy systems of renewable origin.